Effect of Iris Color on the Outcome of Descemet Membrane Endothelial Keratoplasty. Issue 7 (July 2020) - Hayashi, Takahiko; Hos, Deniz; Schrittenlocher, Silvia; Siebelmann, Sebastian; Matthaei, Mario; Franklin, Jeremy; Clahsen, Thomas; Bock, Felix; Bachmann, Björn; Cursiefen, Claus
Abstract : Purpose: To explore the impact of iris color on the outcome of Descemet membrane endothelial keratoplasty (DMEK). Methods: Consecutive cases of Fuchs endothelial dystrophy after DMEK were retrospectively analyzed from the prospective Cologne DMEK database between 2011 and 2017 at the University of Cologne, Germany. Iris pictures were graded by color into blue, green, or brown and compared regarding outcome parameters including best-corrected visual acuity (converted to logarithm of the minimal angle of resolution), central corneal thickness, endothelial cell density (ECD), each at preoperative (baseline) and postoperative 12 months, rebubbling rates, cystoid macular edema (CME), and immune rejections after surgery. Results: One thousand one hundred six eyes of 814 patients were included in this study that consisted of 354 blue eyes, 418 green eyes, and 244 brown eyes. There was no significant correlation between iris color and any parameter (best corrected visual acuity; P = 0.064 at preoperatively, P = 0.959 at 12 months) (ECD; P = 0.158 preoperatively, P = 0.859 at 12 months) (central corneal thickness; P = 0.148 preoperatively, P = 0.252 at 12 months). The loss of ECD at 12 months after surgery was 37.2% ± 1.0% in blue eyes, 37.2% ± 0.9% in green eyes, and 37.2% ± 1.2% in brown eyes ( P = 0.999). Immune rejections were 1.7%, 2.9%, and 0.8% ( P = 0.168) in blue, green, and brown eyes, respectively. Rebubbling rates and CME incidence were similar in each group ( P = 0.129, and P = 0.552 respectively). Conclusions: The iris color has no significant impact on the outcome after DMEK. Thus, DMEK can be applied effectively, regardless of the iris color.